2021
DOI: 10.1038/s41598-021-90861-9
|View full text |Cite
|
Sign up to set email alerts
|

An ERP study on facial emotion processing in young people with subjective memory complaints

Abstract: Subjective memory complaints (SMCs) are commonly related to aging, but they are also presented by young adults. Their neurophysiological mechanisms are not thoroughly understood, although some aspects related to affective state have been mentioned. Here, we investigated whether facial emotion processing is different in young people with (n = 41) and without (n = 39) SMCs who were exposed to positive, negative, and neutral faces, by recording the event-related potential (ERP) activity. From the ERP activity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(64 reference statements)
0
4
0
Order By: Relevance
“… Lozoya-Delgado et al (2012) showed that 21 was the mean score on this questionnaire in a sample of 900 Spanish participants. Based on this result and our previous study ( Perez et al, 2021 ), participants with a score of 21 or higher on the MFE-30 were included in the SMCs group. Participants who scored below 21 were included in the group with no SMCs (noSMCs).…”
Section: Methodsmentioning
confidence: 98%
“… Lozoya-Delgado et al (2012) showed that 21 was the mean score on this questionnaire in a sample of 900 Spanish participants. Based on this result and our previous study ( Perez et al, 2021 ), participants with a score of 21 or higher on the MFE-30 were included in the SMCs group. Participants who scored below 21 were included in the group with no SMCs (noSMCs).…”
Section: Methodsmentioning
confidence: 98%
“…Additionally, gender was also investigated in the present study, as it was also an important facial clue. Compared with the latest recent research about facial expressions [15], the present research used the TG paradigm, which created a more realistic decision-making environment. Therefore, the result would be beneficial for guiding individuals to make rational decisions in real social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the result would be beneficial for guiding individuals to make rational decisions in real social interactions. Meanwhile, the study [15] focused on the gender of the participants. By contrast, we extended the study [15] by exploring the effect of the partner's gender on decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation